Medicine and Public Health, Science and Education Building, New York World's Fair 1939 (Grinnell Litho Co.)
Situated on Constitution Mall and overlooked by the Trylon and Perisphere, these buildings dramatize all phases of Public Health including the operation of the mechanism of the human body. The landscaped court with its unique spiral cascade is enhanced by the beauty of the murals and statuary with which this building is decorated.